Crude bio-glycerol aqueous phase reforming and hydrogenolysis over commercial SiO2Al2O3 nickel catalyst. (November 2016) - Seretis, Antonios; Tsiakaras, Panagiotis
Abstract: In the present work, an one-pot Aqueous Phase Reforming (APR) and Aqueous Phase Hydrogenolysis (APH) of crude glycerol in a batch reactor containing commercial SiO2 Al2 O3 supported 65%Ni catalyst is performed. The effect of: i) the glycerol's impurities, ii) the operating temperature (200–240 °C) and iii) the crude glycerol concentration (10–40 wt%) is investigated. The main gaseous products are H2, CH4 and CO2, while the main liquid products are propylene glycol (PG), ethylene glycol (EG), ethanol and acetol. The selectivities of the gaseous and liquid products are not strongly affected by the addition of low concentration impurities of methanol and sodium chloride. Glycerol's conversion increases as temperature and glycerol's concentration increases. Total conversion for both pure and crude glycerol is >90%. The yield of the most useful liquid product (propylene glycol) is reaching up to 30% for a 40 wt% of crude glycerol solution at T = 240 °C and 4 h of reaction time. Graphical abstract: Highlights: One pot APR+APH of crude bio-glycerol was accomplished. The 65%Ni/SiO2 Al2 O3 catalyst performance using a real crude glycerol feed is examined. The comparison between crude and pure glycerol is presented. The maximum PG yield was up to 30% using a real crude glycerol as a feed.